Peningkatan Breastfeeding Self Efficacy pada Ibu Postpartum Melalui Hypnobreastfeeding - Efa Septiana; Ekta Puspi Sari (FORIKES, 2024)
Breastfeeding self-efficacy is the strongest factor that can influence the breastfeeding process and the success of exclusive breastfeeding. One solution that can help improve breastfeeding self-efficacy is to do hypnobreastfeeding. The purpose of this study was to analyze the effectiveness of hypnobreastfeeding to improve breastfeeding self-efficacy in postpartum mothers. This study was an experimental study with a one group pretest and posttest design, which was conducted in the postpartum room of Demang Sepulau Raya Hospital. This study involved 23 postpartum mothers selected using consecutive sampling techniques. Breastfeeding self-efficacy before and after hypnobreastfeeding was measured by filling out a questionnaire, then the two groups of data were compared using the Wilcoxon test. The results showed that the p-value of the Wilcoxon test was 0.000, so it could be interpreted that there is a difference in breastfeeding self-efficacy between before and after hypnobreastfeeding, with a higher level of breastfeeding self-efficacy in the phase after hypnobreastfeeding. Therefore, it could be concluded that hypnobreastfeeding is effective in increasing breastfeeding self-efficacy in postpartum mothers in the postpartum room of Demang Sepulau Raya Hospital.Keywords: breastfeeding self-efficacy; hypnobreastfeeding; postpartum ABSTRAK Breastfeeding self-efficacy merupakan faktor yang paling kuat yang dapat mempengaruhi proses menyusui dan keberhasilan pemberian air susu ibu eksklusif. Salah satu solusi yang dapat membantu meningkatkan breastfeeding self efficacy adalah dengan melakukan hypnobreastfeeding. Tujuan penelitian ini adalah untuk menganalisis efektifitas hypnobreastfeeding untuk meningkatkan breastfeeding self-efficacy pada ibu pasca melahirkan. Penelitian ini adalah studi eksperimental dengan rancangan one group pretest and posttest, yang dilakukan di ruang nifas RSUD Demang Sepulau Raya. Penelitian ini melibatkan 23 ibu pasca melahirkan yang dipilih dengan teknik consecutive sampling. Breastfeeding self-efficacy sebelum dan sesudah dilakukan hypnobreastfeeding diukur melalui pengisian kuesioner, lalu kedua kelompok data tersebut dibandingkan dengan uji Wilcoxon. Hasil penelitian menunjukkan bahwa nilai p dari uji Wilcoxon adalah 0,000, sehingga bisa dimaknai bahwa ada perbedaan breastfeeding self-efficacy antara sebelum dan sesudah dilakukan hypnobreastfeeding, dengan tingkat breastfeeding self-efficacy lebih tinggi pada fase sesudah dilakukan hypnobreastfeeding. Oleh karena itu dapat disimpulkan bahwa hypnobreastfeeding efektif untuk meningkatkan breastfeeding self-efficacy pada ibu pasca melahirkan di ruang nifas RSUD Demang Sepulau Raya.Kata kunci: breastfeeding self-efficacy; hypnobreastfeeding; pasca melahirkan